Cost-effectiveness of systematic chemotherapy for metastatic pancreatic cancer: a retrospective study using Japanese clinical data - Akira Shinohara; Yuki Takumoto; Junko Tauchi; Koki Morishita; Toshikatsu Kawasaki; Manabu Akazawa (Scientific Reports)
Abstract We compared the cost-effectiveness of gemcitabine plus nab-paclitaxel (GnP) and modified FOLFIRINOX (mFFX)—standard first-line treatments for metastatic pancreatic cancer in Japan. This retrospective cohort study included patients with metastatic pancreatic cancer treated at the National Cancer Center Hospital East in Japan between December 2013 and February 2017. A partitioned survival model, featuring five mutually exclusive health states, was developed. A cost-effectiveness analysis was performed to obtain total costs and quality-adjusted life-years (QALYs). A 2% annual discount rate was applied to costs and outcomes. Parameter uncertainty effect was assessed using a one-way sensitivity analysis. mFFX treatment involved intravenous infusions of oxaliplatin, levofolinate, and irinotecan, whereas GnP treatment involved weekly intravenous administration of nab-paclitaxel and gemcitabine. Dosages were adjusted based on observed adverse events. The total costs of the mFFX and GnP arms were JPY 3,193,597 (USD 31,006) and JPY 3,913,171 (USD 37,992), respectively. Incremental total costs of JPY 719,574 (USD 6,986) were associated with GnP compared to mFFX. Total QALYs were 0.427 and 0.435 for mFFX and GnP, respectively. Therefore, GnP has slightly higher QALYs than mFFX in Japanese real-world clinical practice, suggesting it has a potentially better safety profile, although the impact on healthcare costs persists.